Multifunctional and stretchable graphene/textile composite sensor for human motion monitoring - Zhou,Y; Myant,C; Stewart,R (Journal of Applied Polymer Science, 2022)
Sensors based on electronic textiles (e-textiles) have become increasingly prominent in the field of biomechanical monitoring technology due to multiple properties such as being lightweight, flexible, and comfortable, with increasing potential in incorporating into long-term monitoring devices. Previous research has been conducted into textile strain sensors based on graphene for human motion monitoring, however most graphene e-textile strain sensors exhibit poor sensitivity and stretchability. To our knowledge, no previous research has looked at knitted graphene-based fabrics in regards to the fabric composition of the substrate. In this paper, we propose a graphene/fabric composite sensor using a cost-effective dip coating method of an acrylic/Spandex knit fabric, and further explores its mechanical, electrical, and sensing properties. The developed graphene/textile composite sensor has a wide sensing range (up to 344%) and exhibits a good sensitivity with a high gauge factor of up to 16. As a wearable sensor, our sensing fabric can detect both large and subtle human motions and is able to distinguish between various ranges of joint movements, demonstrating its ability to function as a human motion monitoring system. Our sensor further exhibits the ability to be used as a supercapacitor or capacitive pressure sensor.